SUI GENERIS DALAM PENGGUNAAN GEO STATIONARY ORBIT BERDASARKAN PRINSIP DAN HUKUM RUANG ANGKASA - Sartika Alamsyah, Dwi Putri; Suhartono, Slamet; Nasution, Krisnadi (Faculty of Law, Universitas 17 Agustus 1945 Surabaya, 2020)
AbstractThe purpose of this research is to produce a review related to the exertion of Sui generis Regime in the utilization of Geo Stationary Orbit based on the principles of space law which are examined by comparison of laws and needs between developed and developing countries. This provision was made to provide legal substance related to technical matters and exertion related to the exploration of existing territories in space encompassing the Geo Stationary Orbit slot, and spacecraft skimming. Developing countries strive to be determined